1979
DOI: 10.1017/s0022143000029920
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Basal Water Pressures: Progress and Problemss

Abstract: ABSTRACT. In 1975 and 1977,24 bore holes wer e drilled to the bed o f South Cascade G lacier, Wash ington, U.S.A., using both electrothermal an d hot-water drills. Only two h oles connected d irectly with the basal water syste m, a significant decrease from the four to five such con nections in 13 holes drilled in 1973 and 1974 (H odge, 1976) . Most of the bed, possibly as much as 90 % , appear s to be hyd ra ulically in acti ve an d isolated fr om a few active subgl acial co nduits. Bore h oles whi ch pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 7 publications
(17 reference statements)
6
40
0
2
Order By: Relevance
“…These regions are identified by boreholes that drain slowly when reaching the bed and exhibit diurnal water pressure variations that are out of phase with meltwater input and ice speed4203435363743. In many areas, these inactive regions cover large fractions of the bed; Hodge44 estimated 90% of the bed of South Cascade Glacier in Washington, USA, was hydraulically isolated. This behaviour was observed at all three of the FOXX boreholes, as well as three boreholes at an additional study site420, and boreholes only 30 m apart showed no obvious connection and large hydraulic gradients20, suggesting that weakly connected drainage likely covers most of the GrIS bed in this region.…”
Section: Resultsmentioning
confidence: 99%
“…These regions are identified by boreholes that drain slowly when reaching the bed and exhibit diurnal water pressure variations that are out of phase with meltwater input and ice speed4203435363743. In many areas, these inactive regions cover large fractions of the bed; Hodge44 estimated 90% of the bed of South Cascade Glacier in Washington, USA, was hydraulically isolated. This behaviour was observed at all three of the FOXX boreholes, as well as three boreholes at an additional study site420, and boreholes only 30 m apart showed no obvious connection and large hydraulic gradients20, suggesting that weakly connected drainage likely covers most of the GrIS bed in this region.…”
Section: Resultsmentioning
confidence: 99%
“…Increased basal water pressure reduces N and provides partial support for the weight of the glacier, reducing the contact surface with the underlying bedrock, and thus enhancing basal sliding (Lliboutry, 1958;Hodge, 1979;Iken and Bindschadler, 1986;Fowler, 1987;Schoof, 2005;Gagliardini et al, 2007). A similar effect is observed on glaciers resting on a till layer, where a lower N reduces the yield stress of the till, and thus also enhances basal sliding (sliding is here intended to include motion at shallow depths within the till layer as well as at the ice-till interface) (Engelhardt et al, 1978;Iverson et al, 1999;Tulaczyk et al, 2000;Truffer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Werder et al, 2013), still fail to reproduce direct borehole observations of subglacial conditions . These include the existence of disconnected areas that show no signs of flow-related changes in water pressure (Hodge, 1979;Engelhardt et al, 1978;Murray and Clarke, 1995;Hoffman et al, 2016), the development of widespread areas of high water pressure during winter Harper et al, 2005;Ryser et al, 2014a;Wright et al, 2016), large pressure gradients over short distances (Murray and Clarke, 1995;Iken and Truffer, 1997;Fudge et al, 2008;Andrews et al, 2014), sudden reorganizations of the drainage system (Gordon et al, 1998;Kavanaugh and Clarke, 2000), high spatial heterogeneity, boreholes exhibiting anti-correlated temporal pressure variations (Murray and Clarke, 1995;Gordon et al, 1998;Andrews et al, 2014;Lefeuvre et al, 2015;Ryser et al, 2014a), and englacial conduits (Fountain and Walder, 1998;Nienow et al, 1998b;Gordon et al, 1998;Fountain et al, 2005;Harper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This method uses mainly vertical aerial photography, which records the instantaneous geometry of a glacier, and, if time-sequential photography is available, also the pattern of surface displacement (Meier et al 1985). Bed topography was determined independently (Hodge 1979) from surface radar, direct measurements in boreholes, etc. This report describes a method of using photogrammetric results and compares the estimated mass balances with the independently measured 'true' values.…”
Section: Introductionmentioning
confidence: 99%